Estimacion de la biomasa foliar de Prosopis Flexuosa mediante relaciones alometricas - Ledesma, M.=700 1 Carranza, C.A.; Balzarini, M.
(Es, En)
Ilus., 37 ref.
Keywords: PROSOPIS; CRECIMIENTO; MEDICION; PESO; HOJAS; DIAMETRO; TALLOS; AREA DE SUPERFICIE; ALBURA; ARGENTINA; ALOMETRIA; AGRISCENTIA